2007
DOI: 10.1038/ng2034
|View full text |Cite
|
Sign up to set email alerts
|

MMTV insertional mutagenesis identifies genes, gene families and pathways involved in mammary cancer

Abstract: We performed a high-throughput retroviral insertional mutagenesis screen in mouse mammary tumor virus (MMTV)-induced mammary tumors and identified 33 common insertion sites, of which 17 genes were previously not known to be associated with mammary cancer and 13 had not previously been linked to cancer in general. Although members of the Wnt and fibroblast growth factors (Fgf) families were frequently tagged, our exhaustive screening for MMTV insertion sites uncovered a new repertoire of candidate breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(178 citation statements)
references
References 44 publications
8
170
0
Order By: Relevance
“…models. 1,32 However cyclin E2 mRNA is detected at high levels independently of cyclin E1 mRNA in various malignancies, 20,22 and cyclin E2 repeatedly features in signatures of poor prognosis in breast cancer that do not include cyclin E1. [33][34][35] We show here that cyclins E1 and E2 have distinct effects on progression through mitosis when overexpressed.…”
Section: Resultsmentioning
confidence: 99%
“…models. 1,32 However cyclin E2 mRNA is detected at high levels independently of cyclin E1 mRNA in various malignancies, 20,22 and cyclin E2 repeatedly features in signatures of poor prognosis in breast cancer that do not include cyclin E1. [33][34][35] We show here that cyclins E1 and E2 have distinct effects on progression through mitosis when overexpressed.…”
Section: Resultsmentioning
confidence: 99%
“…For cVIS7 this was caused by the absence of documented genes, while in other cases expression changes as a consequence of the virus integration events were not observed for the immediately adjacent genes (for example cVIS5 and cVIS10). This suggests the existence of yet undefined (non-) coding genes in the vicinity of the virus and/or the long-range action of the integrated virus on distantly located genes [13,14]. In the tamoxifen-resistant cell lines not belonging to a cVIS, the 123 responsible target genes remain to be determined.…”
Section: Insertion Mutagenesis As a Functional Screen For Estrogen Inmentioning
confidence: 99%
“…a small region on the genome with multiple integration events in independent cell clones) strongly indicates that the retrovirus inactivated or modulated expression of a target gene that underlies the selected phenotype. In recent years, large numbers of cVIS have been defined using high throughput technologies for various types of malignancies in mice [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The association between RSPO and cancer has not been extensively studied. It has been reported that RSPO2 and RSPO3 insertional activation is observed in the mouse mammary tumor virus model system (11,12). Administration of RSPO1 protein to mice induces rapid crypt cell proliferation, which causes a marked increase in the size of the small intestine (13).…”
Section: Introductionmentioning
confidence: 99%